Hierarchical Time-Aware Approach for Video Summarization - Cardoso, Leonardo Vilela; Gomes, Gustavo Oliveira Rocha; Guimarães, Silvio Jamil Ferzoli; Patrocínio Júnior, Zenilton Kleber Gonçalves do (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
Video summarization consists of generating a concise video representation that captures all its meaningful information. However, conventional summarization techniques often fall short of capturing all the significant events in a video due to their inability to incorporate the hierarchical structure of the video content. This work proposes an unsupervised method, named Hierarchical Time-aware Summarizer–HieTaSumm, that uses a hierarchical approach for that task. In this regard, hierarchical strategies for video summarization have emerged as a promising solution, in which video content is modeled as a graph to identify keyframes that represent the most relevant information. This approach enables the extraction of the frames that convey the central message of the video, resulting in a more effective and precise summary. Experimental results indicate that the proposed approach has great potential. Specifically, it seems to enhance coherence among different video segments, reducing frame redundancy in the generated summaries, and enhancing the diversity of selected keyframes.